Translating is not (only) problem solving - Munoz Martin, Ricardo; Olalla-Soler (The Journal of Specialised Translation, 2022)
The aims of this article are twofold: to challenge views on translation as problem solving in Cognitive Translation and Interpreting Studies (CTIS), and to outline an alternative approach that calls for tapping and investigating the whole translation process—and not (only) problem solving. We first offer a review of the concepts of problem and problem solving in psychology. Second, we discuss several approaches to problem and problem solving in translation and outline the conceptual troubles of these models. We then focus on the operationalisations of translation problem-solving constructs and discuss how the traditional use of pauses as an indicator of problem-solving stances in translation is troublesome. Finally, we outline an alternative approach to translation as problem-solving from a cognitive-translatological perspective. We approach translation as a type of constrained production of texts led by creative imitation. The overarching constraint is the existence of one or several source texts to which an intertextual relationship of identity is assumed. Such a shift in perspective, we contend, calls for an updated research agenda in CTIS based on considering the whole translation process instead of solely focusing on problem solving, along the lines laid down by cognitive translatology, a situated cognition framework within CTIS.